Oedipus Complex Tokoh Tamura Kafka pada Novel Umibe no Kafuka Karya Murakami Haruki: Tinjauan Psikoseksual Sigmund Freud - I Kadek Antartika; Gede Satya Hermawan; Wiwit Cahyaningrum (Japanology: The Journal of Japanese Studies, 2025)
This study aims to describe the Oedipus Complex in the character Tamura Kafka in the novel "Kafka on the Shore" by Haruki Murakami. This research is a qualitative descriptive study, and the data collection process uses observation and note-taking methods. The theory used in this research is Sigmund Freud's psychosexual theory. The results of the study found that the attachment between Tamura Kafka and his mother during the oral and anal stages led Tamura Kafka to an Oedipus Complex crisis when entering the phallic stage. During the phallic stage, Tamura Kafka experienced conflicts with both of his parents, resulting in estrangement between him and his parents. Consequently, Tamura Kafka was trapped in an internal conflict due to the unfulfilled desire towards his mother as the primary object during the phallic stage. Additionally, Tamura Kafka's lack of identification with both of his parents led to an unresolved Oedipus Complex crisis. The lack of resolution of the Oedipus Complex crisis in Tamura Kafka resulted in a tendency towards Oedipus Complex neurosis during his adolescence.